Conhecimento e atitudes de nutricionistas em relação ao vegetarianismo - NEVES, Darlene do Socorro Silva das (2023)
There are few studies that seek to analyze the knowledge and attitudes about vegetarian diets in Nutrition professionals. At the national level, no works were found on the referred theme. Considering that among Brazilians, 14% over 16 years of age declare themselves vegetarians, the objective of this research was to estimate the knowledge and attitudes of nutritionists in relation to vegetarianism. This is a cross-sectional nonprobabilistic sampling study with 102 nutritionists from the Metropolitan Region of Belém who answered an online questionnaire containing 28 items, 19 in the knowledge category and 9 in the attitudes category. The part dedicated to measuring knowledge included items on the adequacy of macronutrients (proteins), micronutrients and vegetarian diets for different stages of life, in addition to items on the relationship between vegetarianism and health. The questions about attitudes addressed the personal belief in the adequacy of vegetarian diets and about the feelings when dealing professionally with the topic. To characterize the subjects, questions were asked about eating habits, age, time since graduation, aspects of academic training, area of expertise and experience of vegetarianism in professional practice. The result was an avera ge of 64.9±15.2% in questions about knowledge and 65.8±22.6% in attitude. The questions that had the highest percentage of correct answers were those of a general nature, while the more specific ones had the lowest percentages. Most participants think that it is necessary to always combine amino acids in the same meal to form complete proteins, that vegetarians need to supplement iron and that they do not need to supplement vitamin B12, and believe that vegetarian diets are not suitable for sportsmen, pregnant women and nursing mothers. In the age strata, the group that most deviated from the general average was professionals aged 50 and over, reflecting the fact that until the 1990s vegetarianism was still seen as nutritionally insecure. The best percentages of correct answers in the two categories came from ovolactovegetarian nutritionists (10% of the sample). Overall, 46% of participating nutritionists said they had seen an increase in the number of adherents to vegetarianism and were not comfortable answering questions from patients, clients or students about vegetarianism. And 92.2% feel the need for more information on the subject for their professional practice. It was almost unanimous (97% of agreement) that vegetarian diets could have more space in undergraduate courses in the field of Nutrition. It is concluded that most of the nutritionists surveyed have positive attitudes towards vegetarianism. As for the percentages of correct answers in the questions of knowledge, there is a need to pay more attention to the theme and its specificities, in order to better meet the expectations and demands of this growing public.